Search for nucleosynthetic and radiogenic tellurium isotope anomalies in carbonaceous chondrites - Fehr, M; Rehkaemper, M; Halliday, A; Schoenbaechler, M; Hattendorf, B; Guenther, D (2006)
Tellurium isotope data acquired by multiple-collector inductively coupled plasma-mass spectrometry (MC-ICPMS) are presented for sequential acid leachates of the carbonaceous chondrites Orgueil, Murchison, and Allende. Tellurium isotopes are produced by a broad range of nucleosynthetic pathways and they are therefore of particular interest given the isotopic anomalies previously identified for other elements in these meteorites. In addition, the data provide new constraints on the initial solar system abundance of the r-process nuclide 126Sn, which decays to 126Te with a half-life of 234,500 years. The 126Te/128Te ratios of all leachates were found to be identical, within uncertainty, despite variations in 124Sn/128Te of between about 0.002 and 1.4. The data define a 126Sn/124Sn ratio of <7.7 × 10-5 at the time of last isotopic closure, consistent with the value of <18 × 10-5 previously reported for bulk carbonaceous chondrites. How close this is to the initial 126Sn/124Sn ratio of the solar system depends on when the investigated samples last experienced redistribution of Sn and Te. No clear evidence is found for nucleosynthetic anomalies in the abundances of p-, s-, and r-process nuclides. The largest effect detected in this study is a small excess of the r-process nuclide 130Te in a nitric acid leachate of Murchison. This fraction displays an anomalous ε130Te of +3.5 ± 2.5. Although barely resolvable given the analytical uncertainties, this is consistent with the presence of a small excess r-process component or an s-process deficit. The general absence of anomalies contrasts with previous results obtained for K, Cr, Zr, Mo, and Ba isotopes in similar leachates, which display nucleosynthetic anomalies of up to 3.8%. The reason for this discrepancy is unclear but it may reflect volatility and more efficient mixing of Te in the solar nebula. © 2006 Elsevier Inc. All rights reserved.